2020
DOI: 10.1038/s41598-020-76420-8
|View full text |Cite
|
Sign up to set email alerts
|

Utility of shape evolution and displacement in the classification of chronic multiple sclerosis lesions

Abstract: The accurate recognition of multiple sclerosis (MS) lesions is challenged by the high sensitivity and imperfect specificity of MRI. To examine whether longitudinal changes in volume, surface area, 3-dimensional (3D) displacement (i.e. change in lesion position), and 3D deformation (i.e. change in lesion shape) could inform on the origin of supratentorial brain lesions, we prospectively enrolled 23 patients with MS and 11 patients with small vessel disease (SVD) and performed standardized 3-T 3D brain MRI studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Previous studies demonstrated that MS lesions are more likely to take on an ovoid shape, which is not surprising since the veins at the center of these lesions are linear. 27,28 Our results expand on this work by showing that CVS+ lesions are more ovoid, as defined by the FALD measurements, than their CVS− counterparts, and this difference is greater in MS vs non-MS cases. It would be interesting to explore in future work whether simple information gleaned from lesion shape characteristics could be an independent predictor of their CVS status.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies demonstrated that MS lesions are more likely to take on an ovoid shape, which is not surprising since the veins at the center of these lesions are linear. 27,28 Our results expand on this work by showing that CVS+ lesions are more ovoid, as defined by the FALD measurements, than their CVS− counterparts, and this difference is greater in MS vs non-MS cases. It would be interesting to explore in future work whether simple information gleaned from lesion shape characteristics could be an independent predictor of their CVS status.…”
Section: Discussionsupporting
confidence: 77%
“…CVS is not the only surrogate marker for MS and RIS lesions. MS lesions incur deformation and displacement on longitudinal 3D scans, transitioning both in shape and location within the CNS 52 . Changes also influence the direction and magnitude of volume 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the specified region of interest, surface complexity was analyzed using maximum curvature analysis, a metric providing the local maximum curvature on discretized triangular mesh surface representations, using proprietary in-house developed computational topography software. 10,15,20 For the curvature values, zero represented baseline for determining the degree of change between timepoints with negative mean values indicating a more concave surface and positive mean values reflecting more convex features.…”
Section: Methodsmentioning
confidence: 99%